Rethinking Media Ethics in the Digital Age: Toward a Framework for Alternative Media Control - Muzafalu Katamba (Yayasan Lentera Avanya Nagari, 2026)
The growth of alternative media has challenged traditional media practices and structures, enabling new ways for participatory journalism and digital activism. However, the ethical frameworks governing these alternative platforms remain unclear and under theorized, largely operating in an ethical vacuum or borrowing from mainstream media ethics to guide online performances. This article identifies a critical ethical gap in alternative media practices. Through a systematic literature review, it examines the ethical tensions and regulatory gaps that emerge when non-professional actors engage in production of media content for public consumption. This article proposes principles for creating ethical guidelines that match with the values of transparence and inclusivity in the digital age. It guides to understand the present setting of media ethical frameworks, focusing on how ethical frameworks can be transformed to meet digital age’s dynamic nature, helping policymakers, media practitioners, assess the implications and guide future studies. The article concludes that alternative media ethics are inevitable in the current digital environment and they offer theoretical guidance for producers and consumers to be free in the production and consumption of media content especially online content ethically, creating something different from the known mainstream media ethics purposely to help in regulating alternative media in the digital era for better services.